The Development of Islamic Financial Product Innovation in Indonesia: A Literature Review of Trends and Challenges - Siti Nurjanah (PT. Berkah Smart Academica, 2025)
This literature review examines the development of Islamic financial product innovation in Indonesia, focusing on trends and challenges. The study aims to analyze the evolution of Islamic financial products, identify key drivers and obstacles to innovation, and assess the impact of these innovations on financial inclusion and economic growth. The methodology involves a comprehensive review of academic literature, industry reports, and government publications. The findings reveal that the Indonesian Islamic finance sector has experienced significant growth, driven by factors such as increasing awareness of Sharia principles, government support, and technological advancements (Wilson & Belk, 2013). However, challenges persist, including the need for greater product diversification, enhanced regulatory frameworks, and improved financial literacy. The conclusion highlights the importance of continued innovation in Islamic finance to promote financial inclusion, support sustainable economic development, and meet the evolving needs of the Indonesian population.